Illness Perception Mediates the Relationship Between the Severity of Symptoms and Perceived Health Status in Patients With Behçet Disease. Issue 8 (December 2019) - Yankouskaya, Alla; Boughey, Alexandra; McCagh, Jane; Neal, Alison; de Bezenac, Christophe; Davies, Simon J.
Abstract : Objective: The aim of this study was to investigate the relationship between psychological representations of illness, perceived health status, and self-assessment of symptom severity in patients with Behçet disease, a rare long-term incurable condition with unclear etiology. Methods: Using cross-sectional survey design, data on self-administered questionnaires on illness perception, health status, symptoms severity, and demographic characteristics were collected from 273 patients with Behçet disease (age range, 18–65 years). The data were subjected to mediation analysis to test whether cognitive and emotional components of illness perception mediate the relationship between the severity of symptoms and heath status. Results: The results support our hypotheses that cognitive components of illness perception (perceived consequences and identity of the illness) mediate the link between symptom activity and pain, whereas emotional components of the illness (emotional representations about the illness) mediate the relationship between disease activity and perceived energy level. Conclusions: The robustness of these mediation effects suggests potential directions for clinical psychologists and health care practitioners in developing support programs. We supplement our study with Open Access database containing information about type of medication, comorbid mood disorder, and detailed measurement of the severity of BD symptoms for sharing and accumulating multidisciplinary knowledge aiming to support the development of interventions. Addressing psychological aspects of BD will help to manage complex patients effectively. Abstract : Supplemental digital content is available in the text.